Computer-Interpretable Clinical Practice Guidelines - Sonnenberg, F. A.; Hagerty, C. G. (Yearbook of Medical Informatics, 2006)
To provide a comprehensive overview of computerinterpretable guideline (CIG) systems aimed at non-experts. The overview includes the history of efforts to develop CIGs, features of and relationships among current major CIG systems, current status of standards developments pertinent to CIGs and identification of unsolved problems and needs for future researchLiterature re view based on PubMed, AMIA conference proceedings and key references from publications identified. Search terms included practice guidelines, decision support, controlled vocabulary and medical record systems. Papers were reviewed by both authors and summarized narratively.There is a consensus that guideline delivery systems must be integrated with electronic health records (EHRs) to be most effective. Several evolving CIG formalisms have in common, use of a task network model. There is currently no dominant CIG system. The major challenge in development of interoperable CIGs, is agreement on a standard controlled vocabulary. Such standards are under development, but not widely used, particularly in commercial EHR systems. The Virtual Medical Record (VMR) concept has been proposed as a standard that would serve as an intermediary between guideline vocabulary and that used in EHR implementation.CIG systems are in a state of evolution. Standards efforts promise to improve interoperability without compromising innovation. The VMR concept can assist guideline development even before clinical systems routinely adhere to standards. Frontiers for future work include using the principles learned by computer implementation of guidelines to improve the guideline development process and evaluation methods that isolate the effects of specific CIG features.
Keywords: Decision Support Systems; Clinical Practice Guidelines / st [Standards] Programming Languages,Software Design; Vocabulary; Controlled; Medical Records Systems; Computerized